The Influence of the Board of Commissioners Composition on Dividend Policy Islamic Commercial Banks in Indonesia for the 2016-2023 Period - Ramdani, Novia Cahaya; Tamara, Destian Arshad Darulmalshah (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The profits of Sharia Commercial Banks in Indonesia have continued to grow; however, these banks rarely distribute dividends. This condition highlights the important role of the Board of Commissioners in shaping dividend policies. This study aims to examine the effect of the composition of the Board of Commissioners on the dividend policy of Sharia Commercial Banks in Indonesia during the 2016–2023 period. A quantitative approach was employed using the Tobit model, with secondary data as the data source. The study applied saturated sampling, resulting in 16 Sharia Commercial Banks as the research sample. The findings reveal that the age of the board of commissioners has a significant positive impact on dividend policy. In contrast, the board size, proportion of independent commissioners, and frequency of board meetings do not have a significant effect. Nonetheless, when considered collectively, these four independent variables simultaneously influence the dividend policy adopted by the banks.